GESTÃO ESTRATÉGICA DE FRANQUIAS DE VAREJO DE SHOPPING S CENTERS DE SALVADOR UM ESTUDO MULTICASO NAS FRANQUIAS VICTOR HUGO, BOBSTORE E LOCCITANE - Avdzejus, Erica Elena (2011)
This work presents an investigative research that analyses the management of the following franchisint retail stores, Victor Hugo, BobStore and Loccitane, all located in shopping malls in Salvador, Bahia, Brazil. The main general goal of this work is to understand the managerial practices of retail stores in shopping malls. Besides this general goal, we seek, more specifically, to analyze the motivational factors that influences the decision process of opening a franchising, to identify the process of market segment choosing, to verify the difficulties faced during the business opening and managing, to analyze how the managerial aspects of the franchising are carried on, to verify the environmental changes at the franchising stores, to identify the conflicts between the franchisor and the franchisee, and its impacts on the business management, and to evaluate the stores performances and the factors that determine them. On the section dedicated to the methodology we focused mainly on the methodological procedure adopted, which was the multicase study, the one most indicated to investigate such a context directed to contemporary phenomena, inserted in real life situation. The data collection tools used were a research questionnaire, observation and document analysis. For collected data analysis an analytical table was developed with the purpose of presenting the connection between theory and practice in franchising management. We noticed that the success of a franchising business management depend on the market segment chosen, on a good relationship with the franchisor and on the franchisee expertise on providing quick managerial solutions, once, many times, the support provided by the franchisor is not sufficient.